Palladium-Catalyzed Transfer Hydrogenation and Acetylation of N-Heteroarenes with Sodium Hydride as the Reductant - Luo, Fan; Chen, Xiaobei; Yu, Jing; Yin, Yuejia; Hu, Xiaoxiao; Hu, Ying; Liu, Xuejun; Chen, Xiaodong; Zhang, Shilei; Hu, Yanwei (Synthesis, 2023)
An efficient and convenient palladium-catalyzed reductive system by employing sodium hydride as the hydrogen donor and acetic anhydride as an activator has been developed for transfer hydrogenation and acetylation of a wide range of N-heteroarenes including quinoline, phthalazine, quinoxaline, phenazine, phenanthridine, and indole. Moreover, acridine substrates could be directly reduced without the use of acetic anhydride. This protocol provides a simple method for the preparation of various saturated N-heterocycles.
Keywords: palladium; sodium hydride; transfer hydrogenation; N-heteroarenes; N-heterocycles